Punching strengthening of reinforced concrete slab-Column connection using different techniques - Khaleel, Gamal I.; H.Abdel Kareem, Ahmed; S. Debaiky, Ahmed; G.Abd El-maogod, Eslam (International Journal of Advanced Engineering, Management and Science, 2022)
This paper presents experimental data and results on the effect of externally bonded fiber-reinforced polymer (FRP) with studs from FRB on the punching shear behavior of interior slab-column connections. A total of sixteen square slabs with a concentric column were constructed and tested. One specimen act as a control, and the others specimens strengthened with three different strengthening techniques. The first technique consists of 6 slabs strengthened with external FRB strips with different configuration (skewed or orthogonal) and different location from column face (offset or adjacent) and the second technique consist of 4 slab strengthened with external FRB strips with studs from FRP located on both side of the strips with spacing 100 mm and cross at intersection of strips which act as shear reinforcement and wrapping FRP strips to delayed debonding of FRP and improve the structure behavior of strengthened connection. The third technique consists of 5 slabs strengthened with external FRB and steel plates with different size 350 x 350 mm and 450 x 450 mm at the center of the slab. The test variables were the location of FRP strips (adjacent or offset column face), the number of strips layer and the orientation angle of the strips (Orthogonal and Skewed), and the type of materials (GFRP, CFRP, Steel). Size of plate 350 x 350 mm or 450 x 450 mm and method of strengthening. The test results clearly showed that FRP with studs strengthening leads to significant improvements in the structural behavior of slab-column connections. The increase in punching capacity of strengthened slabs was up to 48%, while the increase in stiffness was up to 92% compared to the control slab.